Friedel-Crafts alkylation oxidative cyclization catalyzed by co-oxidation of SeO2 and FeCl3: a simple synthesis of benzo[b]furan from acetophenone and anisole. (2nd January 2023) - Xu, Yuyan; Sun, Jie; Ke, Zhiwei; Li, Ziwei; Tang, Wei; Xu, Yicheng; Chen, Zhiwei
Abstract: A simple one-pot method was developed to complete the α-diphenyl substitution and cyclization of acetophenone using acetophenone and substituted benzene as substrates, and a series of benzofuran derivatives was synthesized efficiently. It had the advantages of medium to excellent yield and easily obtained substrate. Compared with other methods, the method avoids the use of precious metals and cumbersome operations. GRAPHICAL ABSTRACT: UF0001